Metathesis reactions in polymer synthesis - Lyapkov A. A. Aleksey Alekseevich; Kiselev S. A.; Bozhenkova G. S. Galina Sergeevna; Kukurina O. S. Olga Sergeevna; Smirnova N. A. Nataljya Aleksandrovna; Yusubov M. S. Mekhman Suleiman-Ogly (Suleimanovich); Ashirov R. V. Roman Vitaljevich; Verpoort F. V. K. Frensis Valter Kornelius (2018, 2018)
Title screen